ANALISIS KINERJA KEUANGAN PADA HOTEL GRAND ASIA DI MAKASSAR - Ester Tamallo (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
The purpose of this research is to know the financial performance at Hotel Grand Asia in Makassar especially in terms of liquidity ratio and solvency ratio in predicting the condition of financial distresss by using Z-Score Altman method. The method of analysis used in this study is to use the Z-Score Altman formula used: Z '' = 6.56 (X1) + 3.26 (X2) + 6.72 (X3) + 1.05 (X4) Where: Z '' = Overall Index, X1 = Retained Earning / Total Assets, X3 = Earning Before Interest and Taxes / Total Assets, X4 = Book Value of Equity / Total Liabilities. While the results of this study by using the ratio analysis between 2015-2016 obtained good results. It is detected from the increase of several parameters of financial performance. Among the Liquidity Ratios and solvency ratios are increased. Based on the prediction model of Altman Z-Score, Grand Asia Hotel in Makassar is categorized under gray zone conditions or in special attention condition. This is indicated by the Z score or the value of the company's Altman Z-Score index which is below the cut-off value during 2015 until 2016.